ULTRASOUND FINDINGS OF WOMEN PRESENTING WITH INFERTILITY AT TERTIARY CARE HOSPITAL IN PESHAWAR (The Research of Medical Science Review, 2025)
Background: Infertility is presently characterized as a year of unintended non-conception with unprotected sexual intercourse during the fertile phase of menstrual cycles. It refers to the inability of women of reproductive age to conceive due to the consistent penetration of functional, active sperm into the reproductive organs via artificial or natural methods for a period of one year. Objective: To determine the most common pelvic abnormality that causes female infertility. To determine associated history related risk factors (diabetes, hypertension, family history of infertility, late marriages and life style). Method: A descriptive cross sectional study was conducted with non-probability consecutive sampling technique for data collection systematically. Data was collected from 234 female infertile patients that arrive at lady reading hospital for their fertility concerns to determine the most common cause related to female infertility from the study population proceeded at Lady Reading Hospital Peshawar which is the main referral hospital in Peshawar Pakistan. Results: A total of 234 female infertile patients who were referred for ultrasonographic scan were evaluated. The effected age group was 14 to 55 years. The most common cause as found by our study was uterine fibroid and polycystic ovaries being the second leading cause for female infertility. while others including endometriosis, uterine cyst, pelvic inflammatory disease, premature ovarian failure being the less common causes. Also this study assessed various patient history related risk factors. Present study most of the participant were overweight n= 128 (54.7%), normal weight n= 97 (41.5%) and in underweight n=9 (3.8%) which demonstrated obesity as a significant risk factor Conclusion: This study concludes that the most common cause of female infertility as observed on ultrasonography is uterine fibroids while poly cystic ovaries were the second leading cause contributing to female infertility. Ultrasound play an important and essential role in evaluating the cause the female infertility and it also helps in treatment and follow up. Diagnosing the cause of female infertility is very important to proceed with further treatment plan while considering the awareness of infertility risk factors to general public can help to reduce the chances of female infertility.